2018
DOI: 10.1038/s41467-018-06684-2
|View full text |Cite
|
Sign up to set email alerts
|

Microglia innately develop within cerebral organoids

Abstract: Cerebral organoids are 3D stem cell-derived models that can be utilized to study the human brain. The current consensus is that cerebral organoids consist of cells derived from the neuroectodermal lineage. This limits their value and applicability, as mesodermal-derived microglia are important players in neural development and disease. Remarkably, here we show that microglia can innately develop within a cerebral organoid model and display their characteristic ramified morphology. The transcriptome and respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
462
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 467 publications
(484 citation statements)
references
References 42 publications
20
462
2
Order By: Relevance
“…Studies suggest that the possible mechanism underlying neurodegeneration is the chronic inflammation of the CNS induced by the activation of microglia (4,5). Actually, microglia are the resident innate immune cells of the CNS, which originate from the mesoderm lineage and provide innate immunity in the brain (6). Impaired interaction between microglia and DA neurons is increasingly being linked to PD.…”
mentioning
confidence: 99%
“…Studies suggest that the possible mechanism underlying neurodegeneration is the chronic inflammation of the CNS induced by the activation of microglia (4,5). Actually, microglia are the resident innate immune cells of the CNS, which originate from the mesoderm lineage and provide innate immunity in the brain (6). Impaired interaction between microglia and DA neurons is increasingly being linked to PD.…”
mentioning
confidence: 99%
“…Interestingly, a recent study demonstrated that the original Lancaster protocol was perhaps capable of doing this all along (Ormel et al, ). In this report, organoid‐grown microglia (oMGs) were shown to innately develop within BORGs, with only limited alterations to the original protocol published by Lancaster et al ().…”
Section: Approximating the Brain Environment Using Cerebral Organoidsmentioning
confidence: 99%
“…While this makes the model well suited for the study of neurodevelopmental disorders, such as autism (Mariani et al, ; P. Wang et al, ), schizophrenia (Ye et al, ), or ZIKA transmission (Muffat et al, ), it also presents problems when attempting to utilize BORGs and oMGs to study diseases that require a more mature brain environment, such as PD or AD. Ormel et al () also demonstrated that oMGs display a diminished expression levels of the key microglia genes P2RY12 and TMEM119 , further suggesting that these cells have not completely obtained a mature, homeostatic signature. However, this does not mean that oMGs are entirely inappropriate for studying diseases of the developing brain, as it has been shown that the transcriptome may begin to mature as BORGs are aged (Pasca et al, ; Quadrato et al, ).…”
Section: Benefits and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ormel et. al found that microglia innately develop within iPSC‐derived cerebral organoids and showed that those microglia perform similar as primary human microglia in functional assays . Their cerebral organoid protocol is omitting non‐neuronal linage suppression.…”
Section: Ipsc Microglia Protocolsmentioning
confidence: 99%